The Influence of Hydrogen Bond Donors on the CO2 Absorption Mechanism by the Bio-Phenol-Based Deep Eutectic Solvents - Ze Wang; Zonghua Wang; Jie Chen; Congyi Wu; Dezhong Yang (Molecules, 2021)
Recently, deep eutectic solvents (DESs), a new type of solvent, have been studied widely for CO2 capture. In this work, the anion-functionalized deep eutectic solvents composed of phenol-based ionic liquids (ILs) and hydrogen bond donors (HBDs) ethylene glycol (EG) or 4-methylimidazole (4CH3-Im) were synthesized for CO2 capture. The phenol-based ILs used in this study were prepared from bio-derived phenols carvacrol (Car) and thymol (Thy). The CO2 absorption capacities of the DESs were determined. The absorption mechanisms by the DESs were also studied using nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR), and mass spectroscopy. Interestingly, the results indicated that CO2 reacted with both the phenolic anions and EG, generating the phenol-based carbonates and the EG-based carbonates, when CO2 interacted with the DESs formed by the ILs and EG. However, CO2 only reacted with the phenolic anions when the DESs formed by the ILs and 4CH3-Im. The results indicated that the HBDs impacted greatly on the CO2 absorption mechanism, suggesting the mechanism can be tuned by changing the HBDs, and the different reaction pathways may be due to the steric hinderance differences of the functional groups of the HBDs.